The Caucasus : an introduction - De Waal, Thomas (Oxford University Press, 2018)
The Caucasus is an updated version of an essential guide that has introduced thousands of readers to a complex and fascinating region. Thomas de Waal gives a brief and stimulating portrait of Armenia, Azerbaijan, Georgia, their multi-layered history, seemingly intractable conflicts and complex politics.
Keywords: Caucasus -- Politics and government.; Caucasus -- History.; Caucasus -- Relations -- Russia.; Russia -- Relations -- Caucasus.; Caucasus -- Relations -- Soviet Union.; Soviet Union -- Relations -- Caucasus.; Caucase -- Histoire.; HISTORY -- Europe -- Eastern.; HISTORY -- Europe -- Former Soviet Republics.; HISTORY -- Europe -- Russia & the Former Soviet Union.; International relations; Politics and government; Caucasus; Russia; Soviet Union; History